From concept to impact: strategic guidelines for environmental behavior change interventions - Biresselioglu, Mehmet Efe; Demir, Muhittin Hakan (Frontiers in Psychology, 2024)
Interventions aiming at behavioral change are common tools for assessing and stimulating environmentally friendly lifestyles. To obtain representative and scalable results from the interventions, the experimental design of the interventions is crucial. Likewise, an operational plan is significant concerning the coherence and consistency of the interventions and the comparability of the results from different interventions. Such a guideline contributes to the design, execution, and supervision of the interventions, provides standardisation and enhances collaboration with the intervention partners. Intervention guidelines also pertain to the strategic planning of data requirements and collection procedures. Based on the work conducted within the context of the EU-funded ENCHANT project, the guidelines presented in this manuscript are structured based on the key phases of planning and design, implementation, and analysis and reporting. Another key area that needs to be considered and included in the guidelines is the planning necessities for the administrative structure for the interventions. This includes allocating staff roles and responsibilities and potential challenges and obstacles that may arise during implementation. Ethical concerns are also addressed.